Das margens, escritos negros : relações entre literatura periférica e identidade negra - Santos, Elisabete Figueroa dos (Universidade Federal de São Carlos, 2015)
This work aimed to study the manifestations of peripheral literature movement of São Paulo, in its intersections with the race issue, in order to verify the relationships that could be established between Black identity and the joints of this movement. Starting from the assumption that the peripheral soirees would build positive meanings for Black and peripheral identities, we made: a literature review, in order to build a theoretical framework, as well as getting materials published about and for the movement; an ethnographic- inspired research in São Paulo’s poetry sessions, based on systematic observations, whose information was organized in field diaries; semi-structured interviews with 19 activists from three peripheral poetry sessions – Palmarino, Elo da Corrente and Poesia na Brasa –; interviews with the author and poet Fuzzil and, with two participantsof these mentioned soirees; and, finally, we conducted thematic analysis and a triangulation ofinformation to identify the analysis units. We found that the poetry sessions are part of a power struggle arena, which plead-meanings. Through this movement, it is given visibility to the Black bodies and audience to the discourses produced to vent the anguish arising from transit through non-place and the desire to be subject in the first person. The literature thus functions as a vehicle to unveil up topics and deleted elements, and to emphasize other appropriate senses to objects whose meanings were historically negative. The curly hair, maroon origins, the link with the periphery etc. become symbolic benefits. Forge up artistic intellectuals and policies references, oriented for challenging the exclusion landmarks imposed to the outskirts and Blacks, as well as for the production of positive speeches and representations endogenously. By turning into rhymes the stratagems of racism, the nature of Black hair, the rejection to adhere to socially ascribed patterns to Black, and the stories and the desires for overruns, Black protagonists arehighlighted, representing them as holders and producers of knowledge. In this context, literature is armament and poets begin to produce it, in a engaged way to the racial question. We conclude that the research data support our hypothesis. We point out the importance of studies that: I) pay attention to the role of Black women poets (minority) in the peripheral poetic circuit; and II) seek to identify the differences and similarities between contemporary poetic movements of Africa and the Black Diaspora.
Keywords: Literatura periférica; Identidade negra; Representações sociais; Ressignificação; Conhecimento; Peripheral literature; Black ethnic-racial identity; Social representations; Reinterpretation; Knowledge; CIENCIAS HUMANAS::PSICOLOGIA